An Epidemiological Study Of Mechanical Health Hazards Amongst Agricultural Workers In Rural India - Manwani, Vijay Kumar; Pandey, Sachin (International Journal of Occupational Safety and Health, 2016)
Background: Agricultural work is subject to the health risks inherent to a rural environment and at the same time to those deriving from the specific work process involved. India being a country of agriculture, majority of its population is engaged in agriculture based activities in a varied manner either directly or indirectly. This sector of activity being most unorganized, very little attention has been given to the occupational health problems of these workers; though the need of investigation and intervention towards these problems has repeatedly been mentioned. Objective: 1)To find out the demographic distribution of agriculture related mechanical health hazards 2)To find out the magnitude of agriculture related mechanical health hazards 3) To find out the protective measures being used by the agricultural workers for the prevention of mechanical health hazards. 4) To give the necessary recommendations for the prevention of mechanical health hazards. Methods: It is a Cross-Sectional study. The study was conducted from the period of June 2009 to December 2011.. Data Collection: A pilot study was conducted on 10 patients. Data collection was done through asking questionnaire from the patients/relatives (AWs); clinical examination and clinical case records of the patients. Analysis of Data: Data was analyzed in the form of percentage (%) and presented in the tabular form. Chi- square (χ2) test was applied as a test of significance with the help of statistical software SPSS statistics (version- 17) Results: Out of total 53 cases 42 (79.25) were males and 11(20.75) were females. Majority (75.48%) of the respondents were hired laborers followed by own land workers (24.52%). Males (79.25%) were more addicted than females(20.75%). Majority of the cases were due to equipment/ instrument induced (64.15%), followed by animal induced (35.85%) injuries. It was revealed that maximum number of the cases (83.02%)were not using PPE and only 16.98% were using any kind of PPE. International Journal of Occupational Safety and Health, Vol 4 No 2 (2014) 19– 23